Integrative approach for reading comprehension espousing information communication technology literacy - Asdar, Asdar; Hamsiah, Andi; Sujarwo, Sujarwo; Lutfin, Nursamsilis; Sukmawati, Sukmawati (Institute of Advanced Engineering and Science, 2024)
This study aimed to investigate the effects of an integrative approach on students’ reading comprehension, using information and communication technology (ICT) and reading comprehension, the students’ digital literacy and reading comprehension. The quantitative method used an analytical study with cross-sectional research. The data was collected through a questionnaire. There were 473 primary schools with a total of 16,286 children (8,476 male students and 7,810 female students) selected at random as a sample of 400 learners in elementary schools. The findings showed that the integrative approach has a beneficial effect of using ICT and students’ reading comprehension and reading literacy. The use of an integrative approach for reading comprehension and using ICT can promote students’ digital literacy. The student’s reading comprehension and the integrative approach technique were favorable, as seen by the students’ excitement and seriousness. The utilization of this integrative approach can enhance the student’s ability to comprehend reading comprehension and get effectiveness and efficiency of the Indonesian language. This study provides integrated reading-literacy technology (IRLT) that significantly impacts reading comprehension through the use of ICT and an integrative approach in the reading instruction.